Induction of APOBEC3B cytidine deaminase in HTLV-1-infected humanized mice - Yao, Jinchun (Exp Ther Med, 2019)
Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia/lymphoma (ATL). Following viral infection with HTLV-1, certain infected cells exhibit clonal proliferation. Additional genetic and epigenetic changes in these clonally proliferating cells provide them with the selective advantage of growth, which eventually results in ATL. The precise mechanism, however, has yet to be completely elucidated. It has previously been established that APOBEC3 enzymes are potent host-antiviral restriction factors. Conversely, previous studies have reported that the A3B level is increased in tumor virus infections, such as those caused by HBV and HPV, suggesting that A3B exerts a function as a mutagen. Therefore, the present study analyzed the expression of APOBEC3 family members in various HTLV-1 infection states. No significant differences were observed in the expression between healthy donors and patients with HTLV-1-associated myelopathy. Although no significant changes in the expressions of A3C, A3D, A3F and A3G between uninfected and HTLV-1-infected mice were observed, an increased A3B expression was observed in a short-term humanized mouse model following HTLV-1 infection. In a long-term humanized mouse model following HTLV-1 infection, the gene expression array data exhibited an apparent increase in A3B and CADM1, which are indicators of ATL. Collectively, the results of the present study suggest that A3B is likely involved in the development of ATL in HTLV-1-infected humanized mice.